TPA Tamangapa sebagai Sumber Mata Pencaharian: Strategi Adaptasi Ekonomi Masyarakat Kelurahan Tamangapa Kota Makassar - Sakmawati; Salwia; Nurul Jamiah Sidiq; Agung Firmansyah (PT Ininnawa Paramacitra Edukasi, 2026)
This study aims to analyze the role of Tamangapa Final Disposal Site (TPA Tamangapa) as a source of livelihood and to examine the economic adaptation strategies of the community in Tamangapa Subdistrict, Makassar City. The main issue addressed is the community’s dependence on the informal waste sector, which on one hand sustains household needs, but on the other hand poses health risks, income instability, and limited social protection. This research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, while data were analyzed using the interactive model of Miles and Huberman. The findings reveal that TPA Tamangapa has formed a local waste-based economic system supported by social capital and community survival strategies. These activities also contribute to waste reduction through the implementation of reduce, reuse, recycle (3R) practices. The proposed solutions emphasize the importance of community-based empowerment, strengthening business capacities, improving access to microfinance, and developing inclusive policies to create a sustainable livelihood for communities surrounding the landfill. Keywords: TPA Tamangapa, Economic Adaptation Strategies, Informal Community, Community Empowerment, Sustainable Livelihood